2009
DOI: 10.1007/s00376-009-8138-z
|View full text |Cite
|
Sign up to set email alerts
|

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset

Abstract: Accurate sea surface flux measurements are crucial for understanding the global water and energy cycles. The oceanic evaporation, which is a major component of the global oceanic fresh water flux, is useful for predicting oceanic circulation and transport. The global Goddard Satellite-based Surface Turbulent Fluxes Version-2 (GSSTF2; July 1987-December 2000) dateset that was officially released in 2001 has been widely used by scientific community for global energy and water cycle research, and regional and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…In particular, very cloudy or rainy conditions make accurate retrievals of the near-surface wind speed more difficult using SSM/I-based observations ). As noted in Shie et al (2009), the GSSTF2 product has regional biases, but it is consistent with patterns of atmospheric seasonal variability and provides a realistic representation of the surface heat fluxes.…”
Section: Gsstf2bmentioning
confidence: 75%
See 2 more Smart Citations
“…In particular, very cloudy or rainy conditions make accurate retrievals of the near-surface wind speed more difficult using SSM/I-based observations ). As noted in Shie et al (2009), the GSSTF2 product has regional biases, but it is consistent with patterns of atmospheric seasonal variability and provides a realistic representation of the surface heat fluxes.…”
Section: Gsstf2bmentioning
confidence: 75%
“…A review of the bulk flux model and determination of the near-surface variables can be found in Chou et al (2003). Updates to the GSSTF2 for the GSSTF2b product can be found in Shie et al (2009). The SSM/I version 4 wind speeds of Wentz (1997) were used in GSSTF2; GSSTF2b uses version 6 SSM/I wind speeds, and brightness temperatures are used in conjunction with estimates of specific humidity following Chou et al (1995).…”
Section: Gsstf2bmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The change in the simulated surface winds is most apparent in the Southern Hemisphere, where the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF; Shie et al, 2009) surface winds, seen in Fig. 2b, show values near 8 m s −1 , experiment 1 (Fig.…”
Section: Ocean Surface Windsmentioning
confidence: 97%
“…The major limitations of satellite-based flux products for tropical cyclone studies are their relatively coarse spatial and temporal resolution or limited coverage. Highresolution (0.25 ) ocean surface turbulent flux data sets aimed at the regional to hurricane scales have been or are being produced (Shie et al 2009;Liu et al 2011). From these new data sets, improved understanding of the dynamics of air-sea interactions at global to regional scales will emerge, and their impact on operational applications and climate studies will soon be realized.…”
Section: Discussionmentioning
confidence: 98%